Regionalna pomoc publiczna w formie dodatku inwestycyjnego dla przedsiębiorstw w Niemczech - Hybka, Małgorzata (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2013)
The aim of this article is to characterize the conditions of awarding and payment of investment premium for enterprises located in Eastern Germany. This form of state aid is granted to support initial investment projects in the production-related, accommodation services and manufacturing industry. The article describes enterprises entitled to investment premium, its rates and fiscal consequences. In addition it indicates selected analysis evaluating economic implications of the investment premium.